Analisis Pertumbuhan Ekonomi Indonesia - Ahmad Soleh (Universitas Muhammadiyah Jambi, 2016)
The high economic growth and continuous in the long run is a target to be achieved by every country in the world, especially developing countries, without exception of the Indonesian state. In achieving these efforts can be done through various approaches and theory development. research entitled